Neonatal Functional Treatment for Pierre Robin Sequence - Gabriella Galluccio; Valentina Mazzoli; Roberto Vernucci; Alessandro Silvestri; Ersilia Barbato (Galenos Yayinevi, 2019)
Objective:Pierre Robin Sequence (PRS) is a heterogeneous pathological condition characterized by the coexistence of micrognathia, glossoptosis, and cleft palate, resulting in upper airway tract obstruction. Among the treatment modalities, the orthodontic approach is one part of the comprehensive care of those patients and will be present in the treatment modalities during all the growth period of the child.Methods:All patients with PRS observed in the period 2013-2017 were treated with a definite functional approach. The results were retrospectively analyzed with regard to functional outcome, total treatment time, and number of plates provided for a single patient.Results:In all the patients, the indicated treatment protocol has been applied as early impression and plate supply, stimulation of bottle feeding with the use of the plate, eventual substitution of the plate if no more adequate to the transverse and sagittal growth of the palate, and continuing the use until the surgical closure of the cleft. All the patients showed a positive outcome to the proposed treatment approach, evaluated with regard to the incidence of feeding improvement and weight gain, to the limit for the surgical phase, in the absence of adverse effects.Conclusion:The use of a functional obturator plate, removing functional alterations to mandibular growth, reduces and, in some cases, eliminates the need for surgical intervention. As also stated in the literature, if despite the presence of the plate nutritional problems persist, immediate different surgical approaches, mainly mandibular osteodistraction, become necessary.